2012
DOI: 10.1074/jbc.m112.382986
|View full text |Cite
|
Sign up to set email alerts
|

5,6-Dimethylxanthenone-4-acetic Acid (DMXAA) Activates Stimulator of Interferon Gene (STING)-dependent Innate Immune Pathways and Is Regulated by Mitochondrial Membrane Potential

Abstract: Background: 5,6-Dimethylxanthenone-4-acetic acid (DMXAA) activates intracellular signaling through uncharacterized pathways similar to those engaged by bacterial pathogens. Results: Mitochondrial targeting agents and absence of STING impair the response to DMXAA in mouse macrophages. Conclusion: Mitochondrial membrane potential is required for optimal response to DMXAA. Significance: This study illustrates that mitochondrial physiology is pivotal in the host response to DMXAA and possibly bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
146
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 83 publications
(73 reference statements)
8
146
1
2
Order By: Relevance
“…Conversely, a different study demonstrated that phosphorylation of this same Ser-366 site plays a crucial role in activating STING-dependent signaling by facilitating binding of IRF3 to facilitate its phosphorylation by TBK1 (40). Previously, our lab identified mitochondrial membrane potential as a requirement for STING-mediated cytokine expression (22). This suggested the possibility that host mitochondria regulates STING, but our studies did not clarify the mechanism by which this may occur.…”
contrasting
confidence: 43%
See 3 more Smart Citations
“…Conversely, a different study demonstrated that phosphorylation of this same Ser-366 site plays a crucial role in activating STING-dependent signaling by facilitating binding of IRF3 to facilitate its phosphorylation by TBK1 (40). Previously, our lab identified mitochondrial membrane potential as a requirement for STING-mediated cytokine expression (22). This suggested the possibility that host mitochondria regulates STING, but our studies did not clarify the mechanism by which this may occur.…”
contrasting
confidence: 43%
“…Induction in Primary Macrophages-Innate signaling pathways can be regulated at many levels and we have shown previously that the cytokine response to the STING-activating ligand DMXAA is regulated by mitochondrial membrane potential, independent of ATP generation (22). In addition to cellular metabolism, host mitochondria also regulate calcium homeostasis (29), leading us to hypothesize that calcium concentrations alter the response to DMXAA.…”
Section: Inhibition Of Ampk Disrupts Sting-dependent Cytokinementioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical exploration began with the agent 5,6-dimethylxanthenone-4-acetic acid (DMXAA), which was recently demonstrated to directly interact with murine STING [103][104][105][106]. A single intratumoral dose of DMXAA in B16 melanoma-bearing mice was sufficient to promote rejection of most tumors, which was associated with a marked augmentation in the frequency of tumor antigen-specific CD8 + T cells.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%